Analisis Partisipasi Masyarakat Dalam Pencegahan Dan Penanggulangan Kebakaran Pemukiman Sektoral Kecamatan Kebayoran Lama Jakarta Selatan - Ari Pianto; Eka Rofiyanti (Institut Ilmu Sosial dan Manajemen STIAMI, 2021)
Analysis Of Public Participation In Fire Prevention And Management In Sectoral Residential Area, Kebayoran Lama District, South Jakarta. This study proposes determining community participation in fire prevention and control of sectoral settlements, Kebayoran Lama District, South Jakarta. The method used is descriptive with a qualitative approach. The study results show that (1) Public participation in the prevention and control of fires in sectoral settlements, Kebayoran Lama District, South Jakarta, includes direct and indirect participation. Direct participation from the community to become volunteers in the Environmental Fire Resilience System (EFRS) and the Fire Volunteer Line. Moreover, one thing that the public can participate indirectly by coordinating with officers when a fire occurs, (2) Constraints on public participation in the prevention and control of fires in sectoral areas, Kebayoran Lama District, South Jakarta, is mainly related to the timing of socialization and training activities which often clash with daily public activities, (3) One of the efforts that has been made to overcome obstacles to community participation in the prevention and control of fires in sectoral areas, Kebayoran Lama District, South Jakarta, is increasing the frequency of socialization and continuous training.